A novel RUNX1 exon 3 - 7 deletion causing a familial platelet disorder. (17th February 2022) - Almazni, Ibrahim; Chudakou, Pavel; Dawson-Meadows, Alison; Downes, Kate; Freson, Kathleen; Mason, Joanne; Page, Paula; Reay, Kim; Myers, Bethan; Morgan, Neil V
Abstract: Familial Platelet Disorder with associated Myeloid Malignancy (FPDMM) is a rare inherited disorder confirmed with the presence of a pathogenic germline RUNX1 variant and is thought to be heavily underdiagnosed. RUNX1 has also been found to be mutated in up to 10% of adult AML cases and other cell malignancies. We performed targeted next-generation sequencing and subsequent MLPA analysis in a kindred with multiple affected individuals with low platelet counts and a bleeding history. We detected a novel heterozygous exon 3–7 large deletion in the RUNX1 gene in all affected family members which is predicted to remove all of the Runt-homology DNA-binding domain and a portion of the Activation domain. Our results show that the combination of targeted NGS and MLPA analysis is an effective way to detect copy number variants (CNVs) which would be missed by conventional sequencing methods. This precise diagnosis offers the possibility of accurate counseling and clinical management in such patients who could go onto develop other cell malignancies.